2004
DOI: 10.1037/0278-7393.30.2.550
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Age of Acquisition in Visual Word Processing: Further Evidence for the Semantic Hypothesis.

Abstract: They addressed the issue using the semantic Simon paradigm. In this paradigm, participants are instructed to decide whether a stimulus word is printed in uppercase or lowercase letters. However, they have to respond with a verbal label ("living" or "nonliving") that is either congruent with the meaning of the word (e.g., saying "living" to the stimulus DOG) or incongruent (e.g., saying "nonliving" to the stimulus dog). Results showed a significant congruency effect that was stronger for early-acquired words th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
32
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 20 publications
7
32
0
2
Order By: Relevance
“…Consequently, our results contrast the findings of Morrison and Gibbons (2006), who reported reliable age of acquisition effects exclusively for items in the living domain. However, our findings are in line with studies reporting age of acquisition effects in semantic tasks such as category-member verification or object classification (Brysbaert et al, 2000;Ghyselinck, Custers et al, 2004;Holmes & Ellis, 2006;Johnston & Barry, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…Consequently, our results contrast the findings of Morrison and Gibbons (2006), who reported reliable age of acquisition effects exclusively for items in the living domain. However, our findings are in line with studies reporting age of acquisition effects in semantic tasks such as category-member verification or object classification (Brysbaert et al, 2000;Ghyselinck, Custers et al, 2004;Holmes & Ellis, 2006;Johnston & Barry, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…The benefits of early learning in object and word recognition are consistent across both participants and languages, and are U. Urooj et al / NeuroImage 87 (2014) 252-264 253 observed over and above the contributions of other factors such as object familiarity and word frequency (Ghyselinck et al, 2004;Izura et al, 2011;Pérez, 2007). In the only previous neuroimaging study of AoA effects in object recognition, Ellis et al (2006) presented pictures of early and late acquired objects to participants for covert naming.…”
Section: Introductionmentioning
confidence: 63%
“…We propose that the rapid modulation of activation in anterior temporal (semantic) cortex by AoA, and the delayed modulation of activation in visual cortex, underlie differences in the strength of the BOLD responses at those two sites observed by Ellis et al (2006) and that the overall modulation of ventral stream responses accounts for both AoA effects on object naming speed seen in normal, healthy adults (Alario et al, 2005;Cuetos et al, 1999;Ellis and Morrison, 1998;Ghyselinck et al, 2004;Juhasz, 2005) and the superior naming of early-than lateacquired objects seen in patients with damage to ventral and anterior temporal cortex (Ellis, 2011;Lambon Ralph et al, 1998;Woollams, 2012;Woollams et al, 2008). The appearance of a mixture of evoked and induced responses at the two ROIs, and that fact that AoA modulates anterior temporal responses in the evoked component but occipital responses in the induced component, demonstrate the benefits of MEG analysis methods that are sensitive to both phase-locked and nonphase-locked responses and are capable of distinguishing between the two.…”
Section: Discussionmentioning
confidence: 97%
“…As is the case for familiarity, however, the exact role of AoA in processing has since been a matter of extensive debate in the literature, mainly because of its correlation with other factors. Current results suggest that estimates of AoA do significantly predict processing effects once effects of other variables are factored out (e.g., Brysbaert & Ghyselinck, 2006;Cortese & Khanna, 2007;Ghyselinck, Custers, & Brysbaert, 2004), a finding that has numerous implications for models of language acquisition (see Juhasz, 2005, for a comprehensive review). For signed language research, measures of AoA are especially important, since most learners of signed languages do not acquire a signed language from infancy, instead exhibiting a wide variety of acquisition profiles (e.g., Emmorey, 2002).…”
mentioning
confidence: 86%